Effect of Lactic Acid Bacteria Concentration on Modification of Banana Humble Flour by Fermentation - Sito Luthfi Gunawan; Hamid Hamid (Westscience Press, 2023)
Banana weevil is a waste that has not been used much, however banana weevil has content lots of nutrition. So that need effort for utilise the banana weevil so that it can beneficial for society. This study used lactic acid bacteria fermentation method which aims to analyze the characteristics of modified banana weevil flour. Then thinly sliced banana weevil soaked for 2 hours inside sodium metabisulfite solution then soaked again use finished solution mixed with bacteria sour lactate with concentration 0;0,02;0,025;0,03 ml/L. After that hump dried and ground for become flour and tested characteristics. The results showed that the swelling power test level was highest at a concentration of 0.03 ml/L, which was 13.39 grams, the % solubility test was highest at a concentration of 0.03 ml/L with a value of 0.12%, the results of the viscosity test after being modified had the same value, namely of 1.4 mPa.s, for the results of reducing sugar content after being modified it decreased and a result of 4% was obtained.